Independent Learning Program Policies in the Preparation of the Thematic Learning Implementation Plan (RPP) - Syakila, Syarifah Nur Wahyu; Setyowati, Wiwid; Lestari, Dwi Endah (Buana Pendidikan, 2021)
With the development of the era in the era of the industrial revolution 4.0, the world of education continues to develop and improve 21st century competencies. Based on the program initiated by the Minister of Education and Culture of the Republic of Indonesia, the Ministry of Education and Culture has set 4 main policies in the field of national education through the "Independent Learning" program. One of the main points of the policy is related to the Learning Implementation Plan (RPP). Based on this, the writer aims to describe how the policy of the independent learning program is in the preparation of the Thematic Learning Implementation Plan (RPP). The method used in this paper is a descriptive qualitative content analysis method. The writing shows the results that, First, based on the drafting concept in making RPP with the existing format, it is considered more rigid. Thus, the policy of the independent learning program is in trimming the RPP from the original 13 components to only 3 components. It is considered more efficient and effective, which will allow the teacher to have a lot of time to prepare and evaluate the learning process that will be implemented. Second, the preparation of the Learning Implementation Plan (RPP) must have and pay attention to the main principles, namely: (1) efficient, writing RPP is done correctly and does not spend much time and energy; (2) effective, writing lesson plans is done to achieve learning objectives; and (3) student-oriented, RPP writing is carried out by considering the readiness, ability, and learning needs of students in class, so that later it can increase students' interest in learning. Third, simplifying the Learning Implementation Plan (RPP) for thematic learning.